ZL006 protects spinal cord neurons against ischemia-induced oxidative stress through AMPK-PGC-1α-Sirt3 pathway. (September 2017) - Liu, Shu-Guang; Wang, Yun-Mei; Zhang, Yan-Jun; He, Xi-Jing; Ma, Tao; Song, Wei; Zhang, Yu-Min
Abstract: Spinal cord ischemia (SCI) induces a range of cellular and molecular cascades, including activation of glutamate receptors and downstream signaling. Post-synaptic density protein 95 (PSD-95) links neuronal nitric oxide synthase (nNOS) with the N-methyl-d -aspartic acid (NMDA) receptors to form a ternary complex in the CNS. This molecular complex-mediated cytotoxicity has been implicated in brain ischemia, but its role in SCI has not been determined. The goal of the study was to investigate the potential protective effects of ZL006, a small-molecule inhibitor of the PSD-95/nNOS interaction, in an in vitro SCI model induced by oxygen and glucose deprivation (OGD) in cultured spinal cord neurons. We found that ZL006 reduced OGD-induced lactate dehydrogenase (LDH) release, neuronal apoptosis and loss of cell viability. This protection was accompanied by the preservation of mitochondrial function, as evidenced by reduced mitochondrial oxidative stress, attenuated mitochondrial membrane potential (MMP) loss, and enhanced ATP generation. In addition, ZL006 stimulated mitochondrial enzyme activities and SOD2 deacetylation in a Sirt3-dependent manner. The results of western blot analysis showed that ZL006 increased the activation of AMPK-PGC-1α-Sirt3 pathway, and the beneficial effects of ZL006 was partially abolished by AMPK inhibitor and PGC-1α knockdown. Therefore, our present data showed that, by the AMPK-PGC-1α-Sirt3 pathway, ZL006 protects spinal cord neurons against ischemia through reducing mitochondrial oxidative stress to prevent apoptosis. Highlights: ZL006 attenuates OGD-induced neuronal injury in spinal cord neurons. ZL006 inhibits OGD-induced oxidative stress and mitochondrial dysfunction. ZL006 stimulates mitochondrial enzyme and SOD2 deacetylation via Sirt3. ZL006 activates AMPK-PGC-1α-Sirt3 pathway in spinal cord neurons.